ANALISIS NILAI-NILAI PENDIDIKAN DALAM NOVEL “SOKOLA RIMBA” KARYA BUTET MANURUNG - Bergias Pandik Duhar; Sunu Catur Budiyono (Universitas PGRI Adi Buana Surabaya, 2015)
This study aims that the results of this study can provide an objective picture for us and can be used as a rationale in conducting further research on value education related to the values of cultural education, religious education, moral education and social education in Butet's novel Sokola Rimba. Manurung. Based on the formulation of the problem in this study